2010
DOI: 10.1080/02724630903409220
|View full text |Cite
|
Sign up to set email alerts
|

A new rhamphorhynchid pterosaur from the Upper Jurassic of Xinjiang, China, and the phylogenetic relationships of basal pterosaurs

Abstract: ABSTRACT-A new rhamphorhynchid pterosaur species, Sericipterus wucaiwanensis, gen. et sp. nov., is described from the Upper Jurassic part of the Shishugou Formation in the Xinjiang Autonomous Region of northwest China. Pterosaurs from this unit are the earliest and only records of pterosaurs in the Jurassic of northwest China. The individual specimen is one of the largest known among 'rhamphorhynchoids,' or non-pterodactyloid pterosaurs. The holotype comprises an associated skeleton of mostly disarticulated, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 58 publications
5
86
1
Order By: Relevance
“…While pterosaur workers have frequently published diagrams comparing and contrasting the pelves of different pterosaur taxa [21], [50]–[55], pelvic and/or sacral characters are mysteriously near-absent from phylogenetic studies of the group: neither Kellner [56] nor Unwin [57], for example, used a single pelvic character in their whole-pterosaur data sets of 74 and 60 characters, respectively, and pelvic and sacral characters are missing from the analyses of Kellner [58], Lü et al [59] and Wang et al [60]. Three pelvic characters were incorporated into the analyses of non-pterodactyloid pterosaurian data compiled by Unwin [61] and Andres et al [62], and a single character was used by Andres and Ji [63] in their analysis of Pterodactyloidea. These characters concern the proportional length of the anterior iliac process (or preacetabular process), shape of the ischiopubic plate, and the form of the prepubis: they serve to differentiate the condition present in the most basal pterosaurs from the remaining members of the groups.…”
Section: Discussionmentioning
confidence: 99%
“…While pterosaur workers have frequently published diagrams comparing and contrasting the pelves of different pterosaur taxa [21], [50]–[55], pelvic and/or sacral characters are mysteriously near-absent from phylogenetic studies of the group: neither Kellner [56] nor Unwin [57], for example, used a single pelvic character in their whole-pterosaur data sets of 74 and 60 characters, respectively, and pelvic and sacral characters are missing from the analyses of Kellner [58], Lü et al [59] and Wang et al [60]. Three pelvic characters were incorporated into the analyses of non-pterodactyloid pterosaurian data compiled by Unwin [61] and Andres et al [62], and a single character was used by Andres and Ji [63] in their analysis of Pterodactyloidea. These characters concern the proportional length of the anterior iliac process (or preacetabular process), shape of the ischiopubic plate, and the form of the prepubis: they serve to differentiate the condition present in the most basal pterosaurs from the remaining members of the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Eudimorphodon was the first pterosaur to be described from the Triassic and was named from a largely articulated specimen including a nearly complete skull. Nearly all pterosaur workers found Eudimorphodon within the Campylognathoididae (Kellner, 2003;Unwin, 2003;Dalla Vecchia, 2009; but see Andres et al, 2010), outside Rhamphorhynchidae + Pterodactyloidea. The divergent morphology of the dentition and skull bones, Triassic age, and the relatively derived position within Jurassic pterosaur clades illustrates that much of the early evolution of Pterosauria remains hidden.…”
Section: Protosuchus Richardsonimentioning
confidence: 99%
“…Kuhn 1967;Wellnhofer 1978;Wild 1979;Peters 2000;Jenkins et al 2001;Kellner 2003;Unwin 2003;Bennett 2007a;Padian 2008a;Lü et al 2010;Hone et al 2012). Instead, Sereno (1991) and Andres et al (2010) reported Owen (1842) as the author of the name Pterosauria.…”
mentioning
confidence: 99%